Happiness and Health: Associations With Cardiovascular Disease Risk Factors - Shepherd, Janine (Auckland University of Technology, 2011)
Chronic disease is the biggest health issue of our time and cardiovascular disease (CVD) is predicted to be the leading cause of death worldwide by 2030 (World Health Organisation; WHO, 2008). Positive psychology is a relatively new discipline that is interested in positive emotions and provides researchers with the option to study character strengths, virtues, optimism and well-being. The aim of this thesis is to examine the relationships that may exist between CVD risk factors and health behaviours in relation to happiness using a positive psychology lens. Study one aimed to examine relationships between happiness and the individual health behaviours that contribute to the risk of cardiovascular disease (CVD) in a sample of ‘blue collar’ workers (n=195). Participants underwent a CVD risk assessment and answered three questionnaires: the Authentic Happiness Inventory (AHI), a physical activity and nutrition patterns questionnaire, and a demographic survey. Pearson’s correlations were conducted to examine associations between the AHI sum results and each demographic and health variable. No significant associations were found. Analysis of variance revealed small differences in happiness scores by ethnicity (Asian Indians were the happiest ethnic group), total cholesterol and LDL cholesterol (the lower the total cholesterol and LDL cholesterol the higher the happiness score). Bivariable and multivariable logistic regression were used to further examine relationships between variables and AHI classification (lowest versus highest tertile of AHI). After elimination of non-significant factors, only smoking status remained associated with AHI classification (p = 0.016). This indicated that non-smokers are happier than smokers in this sample and this is consistent with other research. There was little evidence of associations between happiness and health variables. Whether this was because of homogeneity in happiness scores or a real lack of association is unclear. Happiness can be difficult to examine and find effects due to the fact that many people report being at least moderately to very happy regardless of how they may actually be feeling. Study two aimed to test the convergent validity and test-retest reliability of a measure of happiness; the AHI with a convenience sample of working adults (n=30). Participants completed the AHI on two consecutive days. On the second day, participants also completed the Satisfaction with Life Scale (SWLS) and the Positive and Negative Affect Scale (PANAS). Exploratory factor analysis was conducted on AHI scores with an additional convenience sample of working adults (n = 222). For the overall AHI sum, the test-retest reliability was strong (ICC = 0.92, p < 0.001). There was a strong positive correlation between AHI and SWLS (r = 0.76, p < 0.005) and between AHI and PANAS positive (r = 0.82, p<0.005), indicating acceptable convergent validity. Findings confirmed the convergent validity and test retest reliability of the AHI and thus it can be used as a measure of happiness among working adults in similar populations. Happiness may not be the best measure of psychological well-being and an alternative known as flourishing was promoted as a new goal of positive psychology. The focus of positive psychology is well-being and the gold standard for measuring well-being is flourishing. The European Social Survey (ESS) is the best current gauge of flourishing and may provide a more complete picture of well-being in population surveys. The ability to measure well-being means Positive Health, a new field proposed by Seligman (2005), could link health with positive psychology to improve health outcomes and well-being. The cross-disciplinary approach of positive health could provide us with the vehicle to take us full circle back to WHO’s optimistic definition of health in 1946 and make it a reality in the not too distant future:“A state of complete positive physical, mental and social wellbeing and not merely the absence of disease or infirmity”, (WHO, 1946).
Keywords: Cardiovascular disease; Risk factors; Happiness; Positive psychology; Public Health; Authentic happiness inventory